Návrh na zlepšení systému odměňování zaměstnanců společnosti Uniagro, s. r. o. - Jelínková, Markéta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Bakalářská práce je zaměřena na problematiku hodnocení a odměňování zaměstnanců. Definuje základní pojmy potřebné pro pochopení řešené problematiky. Popisuje možnosti a formy odměňování zaměstnanců. Text bakalářské práce věnuje svoji pozornost také analýze odměňování a hodnocení zaměstnanců konkrétní společnosti, provedené pomocí dotazníkového šetření. V souladu s provedenou analýzou jsou identifikovány nedostatky stávajícího odměňování. Na základě těchto nedostatků jsou navržena opatření vedoucí ke zlepšení tohoto stávajícího systému odměňování konkrétní společnosti.

The bachelor thesis is focused on the issue of evaluation and remuneration employees. Defines the basic concepts necessary for the understanding of the issues. Describes the options and forms of remuneration employees. The text of the bachelor thesis devotes its attention also to the analysis of the remuneration and evaluation of employees in this concrete company, carried out by means of questionnaires. In accordance with the carried out analysis identifies the deficiencies of current remuneration. On the basis of these shortcomings are proposed meansures to improve the existing system of remuneration of the concrete company.
Proposal for Improving the System of Rewarding Employees of Uniagro, s. r. o.
Keywords: Odměňování; systém odměňování; odměna; motivace; stimulace; zaměstnanec; podnik; výkon.; Remuneration; remuneration system; award; motivation; stimulation; employee; company; performance.